SOS - Save Our Soil - Technical Centre for Agricultural and Rural Cooperation; Inter-American Institute for Cooperation on Agriculture (Inter-American Institute for Cooperation on Agriculture, 2010)
In a Nutshell is designed to contribute to the need for enhancing the supply of and access to information for development. Its focus is on stimulating interest and informing on issues and topics of importance to sustainable agricultural development in Caribbean countries.